Clinical and Radiographic Evaluation of a Commercially Pure Cancellous-Structured Titanium Press Fit Total Hip Prosthetic Stem: Ten-Year Followup of the "Natural Hip" Femoral Stem. (27th January 2014) - Pace, Thomas B.; Karegeannes, James C.; Palmer, M. Jason; Tanner, Stephanie L.; Snider, Rebecca G.
Abstract : This study evaluates the outcomes of 92 hip arthroplasties using a press fit, tapered, split tip, proximally porous ingrowth (CSTi) femoral stem (Zimmer Natural Hip) in consecutive hip arthroplasty patients followed for an average of ten years postoperatively (range 5–16 years). Patients were functionally and radiographically evaluated using Harris Hip Scores and plain radiographs assessing postarthroplasty groin or thigh pain and radiographic signs of stem subsidence, proximal femoral fixation, stress shielding, and related calcar resorption. At followup of 5–10 years, the incidence of groin pain and thigh pain was 9.1% and 3.6%, respectively. This incidence improved over time. Beyond 10 years of followup, groin pain was 2.7% and thigh pain zero. In 89% of cases, there was solid contact between the calcar and the undersurface of the stem collar. Five cases were revised for instability (5.4%). The Harris Hip Scores and the incidence of thigh or groin pain were very favorable compared to other reported press fit total hip arthroplasty stems and not significantly different across a broad age range. There were no cases of stem loosening of failure of bony ingrowth into the stem.